2005
DOI: 10.1002/cne.20610
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of hypocretin (orexin) and melanin‐concentrating hormone in the goldfish brain

Abstract: The orexigenic peptides hypocretin (orexin) and melanin-concentrating hormone (MCH) are involved in the control of food intake and in other homeostatic functions including sleep and arousal. In this article we study the distribution of these peptides in the brain of the goldfish (Carassius auratus), focusing on those regions particularly related to feeding, sleep, and arousal. Although the general distribution of these peptides in goldfish shows many similarities to those described previously in other species,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
47
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 115 publications
(189 reference statements)
9
47
0
Order By: Relevance
“…This result is in line with similar observations from several studies in teleosts, amphibians, reptiles, birds, and mammals [Shibahara et al, 1999;Galas et al, 2001;Phillips-Singh et al, 2003;Kaslin et al, 2004;Huesa et al, 2005;Singletary et al, 2005Singletary et al, , 2006Nixon and Smale, 2007;. In contrast, orexins in specific cells of the adenohypophysis have been reported in human [Blanco et al, 2003], orexin-A in two species of anurans [Yamamoto et al, 2004;Suzuki et al, 2007], and orexin-A and orexin-B in the pituitary of two species of teleost fishes [Amiya et al, 2007;Suzuki et al, 2007Suzuki et al, , 2009.…”
Section: Distribution Of Orexin-ir Fibers In the Brain Of Vertebratessupporting
confidence: 80%
See 2 more Smart Citations
“…This result is in line with similar observations from several studies in teleosts, amphibians, reptiles, birds, and mammals [Shibahara et al, 1999;Galas et al, 2001;Phillips-Singh et al, 2003;Kaslin et al, 2004;Huesa et al, 2005;Singletary et al, 2005Singletary et al, , 2006Nixon and Smale, 2007;. In contrast, orexins in specific cells of the adenohypophysis have been reported in human [Blanco et al, 2003], orexin-A in two species of anurans [Yamamoto et al, 2004;Suzuki et al, 2007], and orexin-A and orexin-B in the pituitary of two species of teleost fishes [Amiya et al, 2007;Suzuki et al, 2007Suzuki et al, , 2009.…”
Section: Distribution Of Orexin-ir Fibers In the Brain Of Vertebratessupporting
confidence: 80%
“…In zebrafish (Danio rerio) , orexin-ir cells are segregated into two populations, one along the third ventricle within the preoptic area and suprachiasmatic nucleus and the other within the anterior hypothalamus [Kaslin et al, 2004;Faraco et al, 2006]. The presence of these cells in the goldfish (Carassius auratus) brain is more restricted and they are located in the anterolateral hypothalamus within the nucleus lateralis tuberis and, more caudally, bordering the third ventricle in the nucleus posterioris periventricularis [Huesa et al, 2005]. The latter nucleus contains the main group of orexin-ir cells in the medaka fish Oryzias latipes [Amiya et al, 2007].…”
Section: Orexin-ir Neurons In the Brain Of Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dorsal population seems to be associated with the paraventricular organ (PVO), within the so-called dorsal area of the lateral recess nucleus, whereas the ventral MCH-expressing population is placed within the ventral part of the lateral recess nucleus. Immunohistochemical studies in the goldfish have also reported the presence of MCH-immunoreactive cell bodies within the lateral part of the lateral tuberal nucleus [34]. However, the latter study did not describe the presence of MCH-producing cells associated to the PVO within the caudal hypothalamus but immunoreactive cell bodies were reported within the zona limitans.…”
Section: Discussionmentioning
confidence: 44%
“…Hypothalamic-hypophyseal neurons in the lateral tuberal nucleus respond strikingly to background color changes and constitute the most prominent MCH-mRNA-expressing cell cluster in the teleost brain [36]. Most of the axons of the MCH-producing cells from the lateral tuberal nucleus project to the pituitary [37] but studies in several species including goldfish have further reported dense MCH innervation within all main brain regions [34]. Evolutionary studies on the organization of MCH perikarya within the hypothalamus have reported that a MCH-producing cell cluster within the lateral tuberal nucleus is first seen in the holostean species, tentatively coinciding with the newly acquired pigmentary role of MCH.…”
Section: Discussionmentioning
confidence: 99%